Organisational factors fostering corporate entrepreneurship: a study of state owned entities in South Africa and Zimbabwe - Musara, Diana Marcellin (My University, 2016)
The purpose of this research is to investigate how organisational factors such as management support, reward/reinforcement and work discretion fosters corporate entrepreneurship at State Owned Entities (SOE) in South Africa and Zimbabwe. Several studies have been conducted on corporate entrepreneurship in the private sector with limited research on the same factors in the public sector, especially in Africa. The Corporate Entrepreneurship Assessment Instrument (CEAI) was used in measuring managers’ perception on management support, reward and reinforcement and work discretion. Four hundred on-line questionnaires were distributed, with a response rate of 169 managers from South African and Zimbabwean state owned entities. An hierarchical multiple regression model was used to analyse the results, which showed that there was a positive and significant relationship between management support, reward/reinforcement and work discretion with innovation, confirming results from previous studies. Occupational level was found to moderate the relationship between management support and innovation and the relationship was found to be strongest at junior management level. No moderation effect was found when reward/reinforcement and work discretion was tested with innovation. Further evidence from the survey results also indicated that Zimbabwean SOEs had higher levels of reward /reinforcement and work discretion than South Africa, but both countries had the same level for management support and innovation. However Zimbabwe had implemented more projects than South Africa, indicating that its SOEs were more entrepreneurial. Finally, when occupational levels were considered, Zimbabwe had higher scores for all the three independent variables, except for innovation, which South Africa was leading at junior management levels. However, the levels at middle and senior management was the same for both countries
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management specialising in Entrepreneurship and New Venture Creation March 2016
Keywords: Organizational effectiveness--South Africa; Organizational effectiveness--Zimbabwe; Entrepreneurship--South Africa; Entrepreneurship--Zimbabwe; Government business enterprises--South Africa; Government business enterprises--Zimbabwe